Students’ Attitude towards Mathematics and its Relationship with Mathematics Achievement - Shakya, Saraswati; Maharjan, Rocky (Mangal Research Journal, 2023)
This study aims to investigate the relationship between students' attitudes towards mathematics and mathematics achievement among secondary-level students at community schools in Kirtipur Municipality. A convenience sampling method was used to choose schools and random sampling method was adopted to select 100 secondary level students, comprising 50 males and 50 females from five community schools in Kirtipur Municipality. The Mathematics Attitude Scale Short Form (MASSF), developed by Yasar, M. (2014), was employed to evaluate individuals' attitudes towards mathematics. Additionally, mathematics test-item was administrated to measure mathematical achievement. The results of this research revealed a statistically significant positive correlation between students' attitudes towards mathematics and their mathematics achievement. The findings suggest that as students' attitudes become more positive, their performance in mathematics tends to exhibit a concurrent increase. Furthermore, regression analysis revealed that variations in students' attitudes towards mathematics could account for about 26% of the variability in mathematical achievement. These outcomes highlight the significance of attitudes as a predictive factor in determining students' success in mathematics. Understanding the relationship between attitudes and achievement can assist educators, policymakers, and stakeholders in developing strategies and interventions aimed at nurturing positive attitudes and improving students' mathematical achievement.